Associations between muscle perfusion and symptoms in knee osteoarthritis: a cross sectional study. Issue 10 (October 2015) - Bandak, E.; Boesen, M.; Bliddal, H.; Riis, R.G.C.; Gudbergsen, H.; Henriksen, M.
Summary: Objective: To investigate the association between muscle perfusion in the peri-articular knee muscles assessed by dynamic contrast enhanced magnetic resonance imaging (DCE-MRI) and symptoms in patients with knee osteoarthritis (KOA). Design: In a cross-sectional setting, muscle perfusion was quantified by DCE-MRI in KOA. Regions of interest (ROI) were drawn around the peri-articular muscles, summed and averaged into one single "Total Muscle Volume" volume of interest (VOI). Symptoms were assessed via the Knee injury and Osteoarthritis Outcome Score (KOOS) (0: worst; 100: best). Results: DCE-MRI and clinical data were analyzed in 94 patients. The typical participant was a woman with a mean age of 65 years, and a body mass index (BMI) of 32 kg/m 2 . Reduced multiple regression models analyzing the association between KOOS and DCE-MRI perfusion variables of Total Muscle Volume showed a statistically significant association between Nvoxel% and KOOS pain (0.41 (SE 0.14); P  = 0.0048). Nvoxel% was defined as the proportion of highly perfused voxels; i.e., the voxels that show an early and rapid increase on the signal intensity vs time curves, reach a plateau state (plateau pattern) and then showing a relatively rapid decline (washout pattern) relative to the total number of voxels within the muscle VOI. Conclusions: More widespread perfusion in the peri-articular knee muscles was associated with less pain in patients with KOA. These results give rise to investigations of the effects of exercise on muscle perfusion and its possible mediating role in the causal pathway between exercise and pain improvements in the conservative management of KOA.